2022
DOI: 10.1007/s12369-022-00946-2
|View full text |Cite|
|
Sign up to set email alerts
|

Utilizing an Emotional Robot Capable of Lip-Syncing in Robot-Assisted Speech Therapy Sessions for Children with Language Disorders

Abstract: This study scrutinizes the impacts of utilizing a socially assistive robot, the RASA robot, during speech therapy sessions for children with language disorders. Two capabilities were developed for the robotic platform to enhance children-robot interactions during speech therapy interventions: facial expression communication (containing recognition and expression) and lip-syncing. Facial expression recognition was conducted by training several well-known CNN architectures on one of the most extensive facial exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Their findings indicated that NAO had potential to increase motivation, and readiness towards learning as well as to improve attention span of children. Another pilot study, using the RASA robot in speech therapy sessions for children with language disorders found further supporting evidence for the potential usability of robots in SLC therapy with children [16]. These studies, however, both presented preliminary exploratory findings with small number of participants.…”
Section: Introductionmentioning
confidence: 92%
“…Their findings indicated that NAO had potential to increase motivation, and readiness towards learning as well as to improve attention span of children. Another pilot study, using the RASA robot in speech therapy sessions for children with language disorders found further supporting evidence for the potential usability of robots in SLC therapy with children [16]. These studies, however, both presented preliminary exploratory findings with small number of participants.…”
Section: Introductionmentioning
confidence: 92%
“…Indeed, gamification has the potential to enhance student motivation and increase engagement (Zourmpakis et al, 2022(Zourmpakis et al, , 2023Papadakis et al, 2022, particularly when combined with social robots (Yang et al, 2023;Tran et al, 2023;Issa et al, 2023). Robots provided many enticements to children, which urge them to continue therapy (Alwadain, Al-Ma'aitah, & Saad, 2020;Spaulding et al, 2018), and interaction with robots has been shown to help children with Autism Spectrum Disorder (ASD) and Delayed Speech Development (DSD) improve their social and communication skills (Bouhali et al, 2023;Amirova et al, 2023;Esfandbod et al, 2023); furthermore, in studies carried out by Warren et al (2015), children with speech disorders responded better to humanoid robots than adult administrators or typically developing counterparts.…”
Section: Robot-assisted Education and Speech Therapymentioning
confidence: 99%
“…14 Esfandbd et al [74] Examine the effects of using RASA robot in speech therapy for children with language disorders.…”
mentioning
confidence: 99%